2003
DOI: 10.1590/s0103-97332003000100012
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of a three-stream quantum-plasma equilibrium

Abstract: We apply the Nyquist method to analyze the stability of small amplitude electrostatic waves in quantum plasmas described by the Wigner-Poisson system. The technique is presented in detail to assess the stability of a threestream equilibrium distribution function. The topology of the Nyquist diagrams is substantially changed with increasing quantum diffraction effects. I IntroductionThe topic of quantum plasmas has received considerable attention in the recent literature [1]- [8]. The main reason for this is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 15 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…Applied to a two stream system, the multistream quantum plasma model predicts some new instabilities (attenuated by statistics, [2]) and provides an overall stabilization mechanism for large wave numbers. The same dispersive and stabilizing contribution appears for quantum effects in three stream plasmas [3]. Similar behavior also occurs for quantum plasmas described within the framework of the Wigner-Poisson system [4,5].…”
Section: Introductionsupporting
confidence: 62%
“…Applied to a two stream system, the multistream quantum plasma model predicts some new instabilities (attenuated by statistics, [2]) and provides an overall stabilization mechanism for large wave numbers. The same dispersive and stabilizing contribution appears for quantum effects in three stream plasmas [3]. Similar behavior also occurs for quantum plasmas described within the framework of the Wigner-Poisson system [4,5].…”
Section: Introductionsupporting
confidence: 62%
“…While the mathematical techniques for the quantum plasma problem are the same as for the classical two-stream plasma, the quantum dispersion relation is more subtle as evidenced by Fig. (3). The above analysis can in principle be pursued on similar problems such as the quantum beam-plasma instability and on theories with a discrete structure such as the quantum multi-stream model.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, a kinetic (Wigner-Poisson) treatment of the problem [2] showed that temperature effects can suppress the quantum instability. The quantum fluid equations have been further applied to several quantum streaming instability problems, like the three-stream quantum plasmas [3], the quantum dusty plasmas [4], the electron-positronion quantum plasmas [5] or the magnetized multi-stream instability [6]. The hydrodynamic formalism has also been applied to the quantum filamentation instability, with [7] or without [8] magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the intermediate regime where quantum effects are not too intense but are nevertheless not negligible, there are situations in which unexpected quantum instabilities can arise. Examples on this are the quantum two-stream and three-stream instabilities, [32][33][34][35] showing unstable modes of pure quantum nature and no classical counterpart. In addition, unlike classical plasmas, there is no Penrose functional determining the linear stability properties of quantum plasmas.…”
Section: Introductionmentioning
confidence: 99%